Preparation, In Vitro Characterization, and Cytotoxicity Evaluation of Polymeric pH-Responsive Hydrogels for Controlled Drug Release - Muhammad Suhail; Jia-Yu Liu; Ming-Chia Hung; I-Hui Chiu; Muhammad Usman Minhas; Pao-Chu Wu (Pharmaceutics, 2022)
The aim of the current investigation was based on the development of pH-responsive hydrogels of chondroitin sulfate, carbopol, and polyvinyl alcohol polymerized with acrylic acid in the presence of ammonium persulfate and ethylene glycol dimethylacrylate for controlled drug delivery. A free radical polymerization technique was used for the preparation of these pH-responsive hydrogels. The gel fraction of the prepared hydrogels was increased with the increase in the chondroitin sulfate, carbopol, polyvinyl alcohol, and acrylic acid content, while the sol-fraction was decreased. Swelling and drug release studies were performed in various pH conditions. Greater swelling and drug release were observed at high pH values (pH 4.6 and 7.4) as compared to low pH value (pH 1.2), representing the pH-responsive nature of the synthesized hydrogels. Porosity and drug loading were increased with the incorporation of high concentrations of hydrogel contents except polyvinyl alcohol, which showed reverse effects. Similarly, biodegradation study reported a slow degradation rate of the prepared hydrogels with the increase in hydrogel constituents. Cytotoxicity study proved the safe use of developed hydrogels as no toxic effect was shown on T84 human colon cancer cells. Similarly, various characterizations, including Fourier transform infrared spectroscopy, thermogravimetric analysis, differential scanning calorimetry, X-ray diffraction, and scanning electron microscopy, were performed for prepared hydrogels. Hence, we could demonstrate that the prepared hydrogels can be used as a promising drug carrier for the controlled delivery of drugs.